Bacteria-enhanced dilute acid pretreatment of lignocellulosic biomass. (December 2017) - Yan, Xu; Wang, Zhongren; Zhang, Kejing; Si, Mengying; Liu, Mingren; Chai, Liyuan; Liu, Xueduan; Shi, Yan
Graphical abstract: Highlights: A new BE-DAP strategy was first introduced for lignocellulose pretreatment. BE-DAP caused significant increase in RS enzymatic digestibility. The enhancement by Cupriavidus basilensis B-8 can reach up to 70% compared to DAP. Physicochemical characterization indicated a bacterial digging mechanism for BE-DAP. Abstract: Pretreatment is indispensable for the large-scale and low-cost bio-products production from lignocellulosic biomass. Herein, a new bacteria-enhanced dilute acid pretreatment (BE-DAP) strategy was introduced. Cupriavidus basilensis B-8 as a potential bacterium for lignin degradation was employed. Multi-scale characterizations on the physicochemical structure of rice straw indicated that Cupriavidus basilensis B-8 could act on the lignin droplets formed in dilute acid pretreatment (DAP), and dig out these droplets to recover cracks and holes on rice straw surface, leaving an opened and porous structure for the easy access of enzyme to inner cellulose. Eventually, the enzymatic digestibility of RS was increased by 35–70% and 173–244% in BE-DAP compared to DAP pretreated and untreated RS, respectively. The BE-DAP strategy, as well as its physicochemical mechanism, opened new perspectives for lignocellulose pretreatment.